Extent of radiosensitization by the PARP inhibitor olaparib depends on its dose, the radiation dose and the integrity of the homologous recombination pathway of tumor cells. Issue 3 (September 2015) - Verhagen, Caroline V.M.; de Haan, Rosemarie; Hageman, Floor; Oostendorp, Tim P.D.; Carli, Annalisa L.E.; O'Connor, Mark J.; Jonkers, Jos; Verheij, Marcel; van den Brekel, Michiel W.; Vens, Conchita
Abstract Background and purpose The PARP inhibitor olaparib is currently tested in clinical phase 1 trials to define safe dose levels in combination with RT. However, certain clinically relevant insights are still lacking. Here we test, while comparing to single agent activity, the olaparib dose and genetic background dependence of olaparib-mediated radiosensitization. Materials and methods Long-term growth inhibition and clonogenic assays were used to assess radiosensitization in BRCA2-deficient and BRCA2-complemented cells and in a panel of human head and neck squamous cell carcinoma cell lines. Results The extent of radiosensitization greatly depended on the olaparib dose, the radiation dose and the homologous recombination status of cells. Olaparib concentrations that resulted in radiosensitization prevented PAR induction by irradiation. Seven hours olaparib exposures were sufficient for radiosensitization. Importantly, the radiosensitizing effects can be observed at much lower olaparib doses than the single agent effects. Conclusion Extrapolation of these data to the clinic suggests that low olaparib doses are sufficient to cause radiosensitization, underlining the potential of the treatment. Here we show that drug doses achieving radiosensitization can greatly differ from those achieving single agent activities, an important consideration when developing combined radiotherapy strategies with novel targeted agents.